2010
DOI: 10.1016/s0140-6736(10)61109-9
|View full text |Cite
|
Sign up to set email alerts
|

Rare chromosomal deletions and duplications in attention-deficit hyperactivity disorder: a genome-wide analysis

Abstract: SummaryBackgroundLarge, rare chromosomal deletions and duplications known as copy number variants (CNVs) have been implicated in neurodevelopmental disorders similar to attention-deficit hyperactivity disorder (ADHD). We aimed to establish whether burden of CNVs was increased in ADHD, and to investigate whether identified CNVs were enriched for loci previously identified in autism and schizophrenia.MethodsWe undertook a genome-wide analysis of CNVs in 410 children with ADHD and 1156 unrelated ethnically matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
422
7
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(461 citation statements)
references
References 38 publications
18
422
7
14
Order By: Relevance
“…30 However, other reports associated this CNV with a variety of neuropsychiatric and neurobehavioral disorders, including autism, schizophrenia, intellectual disabilities, cognitive impairment, attention deficit hyperactivity disorder, and epilepsy, as well as congenital heart defects, skeletal manifestations, and thoracic aortic aneurysms and dissections. [31][32][33][34][35][36][37] We suggest that this duplication may contribute to the autistic features seen in patient 7.…”
Section: Discussionmentioning
confidence: 71%
“…30 However, other reports associated this CNV with a variety of neuropsychiatric and neurobehavioral disorders, including autism, schizophrenia, intellectual disabilities, cognitive impairment, attention deficit hyperactivity disorder, and epilepsy, as well as congenital heart defects, skeletal manifestations, and thoracic aortic aneurysms and dissections. [31][32][33][34][35][36][37] We suggest that this duplication may contribute to the autistic features seen in patient 7.…”
Section: Discussionmentioning
confidence: 71%
“…Of the eight articles supporting a major genetic causation for ADHD, only one echoed a scientific study. On 2 October 2010, the most respected French newspaper Le Monde echoed a study published in the prestigious medical journal The Lancet and claiming that DNA deletions or duplications are twice as frequent in ADHD children as in unaffected ones (Williams et al, 2010). Actually, the medical relevance of this study was weak: these DNA alterations were detected in 12.5% of ADHD children and 7.5% of unaffected ones.…”
Section: Resultsmentioning
confidence: 99%
“…Using an isolated population provides increased power to our study to detect rare variants, which increasingly are being identified for common complex disorders. 36,37 Isolated populations might pose an advantage over outbreed populations in detecting rare variants, 38 as only a low number of each risk alleles is likely to be introduced into an isolated founder population. In this way, heterogeneity will be reduced, and the LD surrounding the risk variant will be confined to the population history of the isolate.…”
Section: Discussionmentioning
confidence: 99%